Perceptual Disturbances and Disorders in the ICD-11: An Overview and a Proposal for Systematic Classification - Berthold Langguth; Michael Landgrebe; Dirk De Ridder (Brain Sciences)
The International Classification of Diseases (ICD) has been developed and edited by the World Health Organisation and represents the global standard for recording health information and causes of death. The ICD-11 is the eleventh revision and came into effect on 1 January 2022. Perceptual disturbances refer to abnormalities in the way sensory information is interpreted by the brain, leading to distortions in the perception of reality. These can manifest as distorted perceptions or as phantom perceptions and can occur in all sensory modalities as visual, auditory, olfactory, gustatory tactile, vestibular, proprioceptory or interoceptory disturbances. There are similar brain mechanisms involved in the generation of these analogous perceptual disturbances and disorders, and they are treated with similar approaches. Perceptual disturbances are highly prevalent, with large variations across the different sensory modalities. They can be associated with significant suffering and cause a high socioeconomic burden. Perceptual disturbances can be symptoms of another disease or disease entities on their own. In the context of pain, this is reflected by the distinction between secondary pain (pain as a symptom of another underlying condition) and primary pain (a disease in its own right, rather than being a symptom of another underlying condition) in the ICD-11. Such a clear distinction is not found in an entirely consistent way across the various sensory modalities. By using the example of auditory phantom perceptions, we propose a framework for the classification of sensory disorders in alignment with the classification of pain in the ICD-11. The descriptions of the sensory disturbances should include (1) a causal aspect (primary versus secondary), (2) a temporal aspect (acute vs. chronic and persistent vs. intermittent), (3) a cognitive, emotional and autonomic interpretation aspect (=suffering) and (4) a social aspect (=disability). If the latter two aspects are present, we propose that the sensory disturbance is called a sensory disorder.